Increased investment in Universal Health Coverage in Sub-Saharan Africa is crucial to attain the Sustainable Development Goal 3 targets on maternal and child health - Robert Kokou Dowou; Hubert Amu; Farrukh Ishaque Saah; Oluwafemi Adeagbo; Luchuo Engelbert Bain (BMC, 2023)
Abstract Universal Health Coverage (UHC) is considered a strategic component of the Sustainable Development Goals specifically for goal 3 which seeks to ensure healthy lives and promote well-being for all, where all individuals and communities have equal access to key promotive, preventive, curative, and rehabilitative health interventions without financial constraints. Despite Sub-Saharan Africa (SSA) accelerated gains on the UHC effective coverage of 2.6% between 2010 to 2019, many countries in the sub-region show lagging performance. The major challenges faced in attaining the UHC in many countries include inadequate capital investment for health and their equitable distribution, fiscal space to finance UHC policies and programs. This paper discusses how increased investment in Universal Health Coverage in SSA is crucial to attain the Sustainable Development Goal 3 targets on maternal and child health. The Universal Health Monitoring Framework (UHMF) is adopted in this paper as the underpinning framework. The delivery of essential maternal and child health services to achieve UHC in SSA requires strategic actions such as policies, plans and programs with focus on maternal and child health. We report findings from recently published papers that clearly highlighted the strong connection between health insurance coverage and maternal health care utilization. Strategic actions such as implementing national health insurance scheme (NHIS) that directly incorporates free maternal and child health care could strengthen maternal health services and transform health systems in order to achieve UHC in SSA. We argue that achieving the SDG 3 on maternal and child health will only be possible if significant progress in made in increasing UHC. This is key to ensure optimal maternal health care utilization, and consequently reducing maternal and child deaths.